2021
DOI: 10.3390/ijms22073460
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Evaluation of Antibody-Based Targeted Delivery of Interleukin 9 in Experimental Pulmonary Hypertension

Abstract: Background and Aims: Pulmonary hypertension (PH) is a heterogeneous disorder associated with poor prognosis. For the majority of patients, only limited therapeutic options are available. Thus, there is great interest to develop novel treatment strategies focusing on pulmonary vascular and right ventricular remodeling. Interleukin 9 (IL9) is a pleiotropic cytokine with pro- and anti-inflammatory functions. The aim of this study was to evaluate the therapeutic activity of F8IL9F8 consisting of IL9 fused to the F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 60 publications
(35 reference statements)
2
17
0
Order By: Relevance
“…This goes in line with recent findings of our group showing a strong re-expression of the molecule in human tissue and serum samples from patients suffering from, e.g., coronary artery disease, aortic stenosis, heart failure of different aetiology or rejection after heart transplantation [26][27][28]30,33,36]. Moreover, we could report similar findings in several preclinical models of cardiac allograft vasculopathy or PH, respectively [29,31,32,37]. In a very recent study, including elderly patients suffering from severe symptomatic aortic stenosis, our group investigated a panel of biomarkers with respect to their association to the novel staging classification of extra-valvular cardiac damage [38].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This goes in line with recent findings of our group showing a strong re-expression of the molecule in human tissue and serum samples from patients suffering from, e.g., coronary artery disease, aortic stenosis, heart failure of different aetiology or rejection after heart transplantation [26][27][28]30,33,36]. Moreover, we could report similar findings in several preclinical models of cardiac allograft vasculopathy or PH, respectively [29,31,32,37]. In a very recent study, including elderly patients suffering from severe symptomatic aortic stenosis, our group investigated a panel of biomarkers with respect to their association to the novel staging classification of extra-valvular cardiac damage [38].…”
Section: Discussionsupporting
confidence: 92%
“…From our current data, we cannot state this interesting point concludingly. However, in recent studies of our group, we could show in preclinical animal models of PH that ED-A + Fn is re-expressed both in the pulmonary vasculature as well as in the remodelled right ventricle [31,32].…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…In recent years, a large number of studies have confirmed that the immune response triggered by a myocardial injury, myocardial ischemia, and other factors can produce a variety of cytokines ( 15 ), and most of them, especially the inflammatory cytokines, including tumor necrosis factor α (TNF-α), interleukin (IL)-6, IL-1β, and IL-10 are involved in the occurrence and development of VR ( 13 , 16 ). The major inflammatory cytokines that promote VR are TNF-α, IL-1β, and IL-6.…”
Section: Molecular Pathways Involved In Cardiac Remodelingmentioning
confidence: 99%
“…Pulmonary arterial hypertension (PAH) is a rare vascular disease with an annual incidence of two cases per million (Peacock et al, 2007). PAH is defined by a mean pulmonary arterial pressure (mPAP) > 20 mmHg at rest, a pulmonary artery wedge pressure (PAWP) ≤ 15 mmHg, and a pulmonary vascular resistance (PVR) ≥ 3.0 Wood units (Gouyou et al, 2021). As an obliterative vasculopathy, PAH is characterized by high pulmonary arterial pressure, resulting in right ventricular failure and even death (Boucly et al, 2017;Tang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%